Effect of Native Humic Acids from Tomsk Region Lowland Peat on Mitochrondrial Oxidative Phosphorylation Under Hypoxic Conditions; Pharmaceutical Chemistry Journal; Vol. 49, iss. 4 - Belousov M. V. Mikhail Valerievich; Akhmedzhanov R. R. Rafik Raviljevich; Zykova M. V.; Vasil'ev K. Yu.; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2015, 2015)
Title screen